Carroll–Field–Jackiw term in a massless Rarita-Schwinger model - M. Gomes; J.G. Lima; T. Mariz; J.R. Nascimento; A.Yu. Petrov (Physics Letters B)
We consider the massless Rarita-Schwinger (RS) LV QED. In this theory, we introduce the gauge fixing to obtain the propagator for the RS field, and calculate the Carroll-Field-Jackiw term, which turns out to be finite and ambiguous, and only in one calculation scheme, based on the nonlinear gauge framework, the gauge independence of the result is achieved.